2014
DOI: 10.1111/jbg.12078
|View full text |Cite
|
Sign up to set email alerts
|

Investigating maternal effects on production traits in Duroc pigs using animal and sire models

Abstract: Variance components for production traits were estimated using different models to evaluate maternal effects. Data analysed were records from the South African pig performance testing scheme on 22 224 pigs from 18 herds, tested between 1990 and 2008. The traits analysed were backfat thickness (BFAT), test period weight gain (TPG), lifetime weight gain (LTG), test period feed conversion ratio (FCR) and age at slaughter (AGES). Data analyses were performed by REML procedures in ASREML, where random effects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…The correlation between the direct and maternal genetic effects for BW, BW, and PW in the Yorkshire and Landrace breeds was moderate and negative. These moderate and negative correlations were in agreement with the literature (Arango et al, 2006;Roehe et al, 2010;Dube et al, 2014;Dufrasne et al, 2014). The negative correlation between the direct and maternal genetic effects suggest antagonism between these effects.…”
Section: Discussionsupporting
confidence: 93%
“…The correlation between the direct and maternal genetic effects for BW, BW, and PW in the Yorkshire and Landrace breeds was moderate and negative. These moderate and negative correlations were in agreement with the literature (Arango et al, 2006;Roehe et al, 2010;Dube et al, 2014;Dufrasne et al, 2014). The negative correlation between the direct and maternal genetic effects suggest antagonism between these effects.…”
Section: Discussionsupporting
confidence: 93%
“…These estimates Cabling et al (2015) in 690 finishing Duroc pigs (0.65, 0.41 and 0.73 for BF, LMA and LP, respectively). Moreover, Do et al (2013) and Dube et al (2014) reported an estimate of heritability of 0.54 and 0.48 for BF, respectively. However, Guo et al (2016) estimated the heritability for BF ranging from 0.30 to 0.32.…”
Section: Resultsmentioning
confidence: 99%
“…It might be beneficial for efficient breeding that some traits are affected by maternal genetic effect (David et al., 2015; Roehe & Kennedy, 1993; Satoh et al., 2002), although we cannot suggest why a non‐zero direct‐maternal genetic correlation was estimated only for BL. Interpreting negative estimates of direct‐maternal genetic correlation has been discussed in terms of biological mechanism, data structure and other factors (Bijma, 2006; David et al., 2015; Dodenhoff, Van Vleck, & Wilson, 1999; Dube et al., 2014; Heydarpour, Schaeffer, & Yazdi, 2008; Lee & Pollak, 1997; Maniatis & Pollott, 2003; Robinson, 1996; Willham, 1980). As an additional analysis, we ran 200 simulations of the phenotypic data of 2,835 pigs with a direct heritability of 0.3 and without maternal genetic or common litter environmental effect, based on the pedigree information of 11,631 pigs, with an infinitesimal model (Bulmer, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…Substantial effects of a shared environment on phenotypic measurements in younger pigs have been reported, such as common litter environmental effects and maternal genetic effects (Flori et al., 2011; Hoque, Suzuki, Kadowaki, Shibata, & Oikawa, 2007; Suzuki et al., 2005; Tomiyama, Kanetani, Tatsukawa, Mori, & Oikawa, 2010; Yang et al., 2018). Statistical models that ignore maternal effects might bias estimates of direct heritability (Dube, Mulugeta, & Dzama, 2014; Satoh, Hicks, Ishii, & Furukawa, 2002). Therefore, it is important to choose an appropriate model for accurate genetic parameter estimation.…”
Section: Introductionmentioning
confidence: 99%